2009
DOI: 10.1097/nan.0b013e3181bd519e
|View full text |Cite
|
Sign up to set email alerts
|

The Resurgence of Granulocyte Transfusions

Abstract: Granulocyte transfusion can be used as supportive therapy in patients with life-threatening neutropenia caused by bone marrow failure or in patients with neutrophil dysfunction. Emerging evidence demonstrates the benefits of granulocyte transfusions to treat infections in patients after treatment with high-dose chemotherapy, particularly the chemotherapy associated with conditioning for hematopoietic stem cell transplant. There has been an increased interest in the use of therapeutic granulocyte transfusion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In patients with haematological malignancies (HM), plenty of factors, including dose-intensive chemotherapy and haematopoietic stem cell transplantation (HSCT), may cause severe and persistent neutropenia, resulting in the risk of a compromised immune system and increased susceptibility to opportunistic and life-threatening bacterial and fungal infections. Granulocyte transfusions (GTx), which have been in use for more than 50 years, seem to be a sensible therapeutic approach to this problem [1,2]. The theoretical potential for granulocyte transfusion was established by early animal studies, which showed that granulocytes transfused to neutropenic dogs were of normal appearance and viability and migrated to the sites of infection [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with haematological malignancies (HM), plenty of factors, including dose-intensive chemotherapy and haematopoietic stem cell transplantation (HSCT), may cause severe and persistent neutropenia, resulting in the risk of a compromised immune system and increased susceptibility to opportunistic and life-threatening bacterial and fungal infections. Granulocyte transfusions (GTx), which have been in use for more than 50 years, seem to be a sensible therapeutic approach to this problem [1,2]. The theoretical potential for granulocyte transfusion was established by early animal studies, which showed that granulocytes transfused to neutropenic dogs were of normal appearance and viability and migrated to the sites of infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…This was the first known use of GTx in humans [6]. Due to the transfusion of malignant cells, this method is contentious to readers today, yet it was thought to be a realistic choice at the time [2,7].…”
Section: Introductionmentioning
confidence: 99%